Living Together as a Contemporary Social Phenomenon: A Critical Analysis from the Perspectives of Islamic Law and Indonesian Legal Regulations - Muhamad; Taufid Hidayat Nazar (Syakhsiyah Jurnal Hukum Keluarga Islam, 2026)
Living together, or cohabitation, has become a contemporary social phenomenon that challenges the normative foundations of family, morality, and criminal regulation in Indonesia. This article aims to critically examine living together from the perspective of Islamic law and Indonesian legal regulation, particularly Article 412 of Law Number 1 of 2023 concerning the Criminal Code. This study employs a qualitative library research method with a normative-critical approach. The analysis is constructed through Islamic legal principles, including nahi munkar, ḥifẓ al-nasl, maṣlaḥah-mafsadah, and ta‘zīrī policy, while also examining the legal construction of cohabitation as regulated in the new Criminal Code. The findings show that Islamic law views living together without a valid marriage contract as contrary to the protection of honor, lineage, family responsibility, and the prevention of acts leading to zina. However, Article 412 of the Criminal Code cannot be simply equated with the Islamic punishment for zina, since it is closer to a form of state regulation within the framework of ta‘zīr and public order. The article concludes that the regulation of living together may be justified in Islamic legal reasoning insofar as it is applied proportionally, protects family values, ensures legal certainty, limits excessive state intervention into private life, and prevents greater harm in law enforcement.